Cintigrafia de Perfusão Miocárdica no Enfarte do Miocárdio: Impacto da elevação do segmento ST e da Diabetes mellitus - João Miguel Portugal Antas de Barros Barbosa (2021)
Myocardial perfusion scintigraphy (MPS) is frequently used in the evaluation of patients with myocardial infarction (MI). The goal of the present work was to evaluate changes in MPS according to the nature of the infarction (ST elevation versus non-ST elevation status) as well as according to the presence or absence of Diabetes mellitus. A prospective study of 124 consecutive patients with MI was carried out, using MPS. Patients with ST segment elevation MI (STEMI) had significantly larger values both for percentage and absolute areas of perfusion defects, both at rest and in stress situation, when compared to patients without ST segment elevation (NSTEMI). These patients had significantly lower values for left ventricular ejection fractions (EF), in a similar comparison. The values for perfusion defects at rest for STEMI patients was more than double the values for NSTEMI patients (17.1+14.6% versus 6.5+7.8%, p <0.001). Concerning resting left ventricular EF, STEMI patients had a mean value of 47.6+13.6% and NSTEMI patients had a mean value of 53.2+12.4% (p 0.026). Regarding the comparison between patients with and without Diabetes mellitus, none of the parameters under study showed significant differences. Linear regression analysis, taking percentage of perfusion defect as dependent variable, yielded an overall significant result, however only ST segment elevation was shown to have an individually significant result. We conclude that the presence of ST segment elevation but not the presence of Diabetes mellitus is associated to different patterns of MPS in patients with MI.